2002
DOI: 10.1111/j.1572-0241.2002.07068.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of Peptic Ulcer Disease Not Related to Helicobacter pylori or NSAIDs

Abstract: Helicobacter pylori (H. pylori) infection is widely accepted as the most important factor in the pathogenesis of duodenal ulcer. However, in parallel with more effective eradication of H. pylori, the prevalence of H. pylori is changing, and H. pylori-negative peptic ulcer disease appears to be increasing. When making a diagnosis of H. pylori-negative peptic ulcer disease, it is essential to avoid misclassification because of inaccurate diagnosis. In addition, secondary causes may need to be excluded with appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
49
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 93 publications
3
49
0
2
Order By: Relevance
“…A meta-analysis of seven double blind, randomized trials in North America found that 20% of patients with H. pylori-associated ulcers had ulcer recurrence within 6 months despite successful H. pylori eradication and no reported NSAID use (37)(38)(39) . No role could be proposed for the smoking habit on the basis of two studies, either on non-H. pylori and non-NSAID duodenal ulcers or on H. pylori-associated ulcers (49,63) . In developed countries there was wide variation in the rates of DUP and of infection by H. pylori.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of seven double blind, randomized trials in North America found that 20% of patients with H. pylori-associated ulcers had ulcer recurrence within 6 months despite successful H. pylori eradication and no reported NSAID use (37)(38)(39) . No role could be proposed for the smoking habit on the basis of two studies, either on non-H. pylori and non-NSAID duodenal ulcers or on H. pylori-associated ulcers (49,63) . In developed countries there was wide variation in the rates of DUP and of infection by H. pylori.…”
Section: Resultsmentioning
confidence: 99%
“…Results from the USA suggest that the proportion of H. pylori-negative ulcer, while varying somewhat, appears to be rising (60) ; the prevalence of infection in some regions may be of only 30%, and about 20% of the PUD patients are not infected (45) . Quan and Talley (49) systematically reviewed the prevalence of unexplained ulceration in the period between 1995 and 2001, finding that a relevant proportion of PUD patients were not infected by H. pylori. Other studies in the USA showed that 20% to 50% of the peptic ulcers were not related to H. pylori infection or to the use of NSAID (14,15,23,25) .…”
Section: Resultsmentioning
confidence: 99%
“…Gastric ulcer is believed to be due to an imbalance between aggressive and mucosal integrity factors. Increase of aggressive factors (gastric acid and pepsin secretion) and decrease of mucosal integrity factors (inhibition of prostaglandin, decrease of bicarbonate concentration, and diminished of blood flow in gastric) have potential against developed of gastric ulcer [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Múlti-ples estudios han demostrado que esta bacteria es un factor de riesgo fundamental en la UP. En este sentido, se ha hallado que cerca del 95% y 85% de las personas con UD y UG respectivamente están infectadas, y que la erradicación de la bacteria aumenta la tasa de curación de este problema de salud y reduce de forma significativa las recaídas (Quan y Talley, 2002). Así mismo, se ha podido determinar que hay una relación temporal entre la gastritis asociada a la H. pylori y el origen de la UP; que la probabilidad de desarrollar la UP aumenta a mayor exposición a la H. pylori, y que hay una serie de mecanismos fisiopatológicos asociados a la bacteria que explican su relación con esta condición médica (p.ej., la inflamación de la mucosa gástrica y las alteraciones en la actividad ácido-péptica) (Gisbert, Boixeda y Martín de Argila, 1996).…”
Section: Introductionunclassified